Interlanguage discourse of thesis acknowledgements section examining the terms of address - Basthomi, Yazid (2008)
The present article address es the under-researched issue of the use of terms of address in the (sub) genre of thesis acknowledgements sections written in English by Indonesian students of English as a Foreign Language (EFL). The corpus was composed of acknowledgments sections of 40 theses available at the State University of Malang, Indonesia. Focal to the findings is the notion that the thesis writers tend to use full-fledged academic titles in addressing the parties who have immediate contributions to the completion of the thesis. Those peripheral to the thesis completion are addressed using or alternatively without academic titles. The findings show that the seemingly respectful acknowledgements are not necessarily that innocently reverential. The findings also demonstrate that solidarity in social relations does not necessarily lead the writers to use neutral and/or endearing forms of address. This latter point puts a challenge to the conventional conceptions of "power" and "solidarity."
Includes bibliographical references (pages 63-65).